THE EFFECT OF JOB SATISFACTION TO ORGANIZATIONAL COMMITMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Kerisna, Made Adhi; Suana, I Wayan (E-Jurnal Manajemen; Vol 6 No 7 (2017), 2017)
The purpose of this study is to determine the effect of job satisfaction on organizational commitment and organizational citizenship behavior on the employees of Cooperatives and SMEs of Bali Province. This research was conducted at Department of Cooperatives and UMKM of Bali Province by using 84 people as research respondents. Sample determination technique used in this research is saturated sample technique. Data analysis technique used in this research is path analysis processed using SPSS software. Based on the path analysis can be concluded that job satisfaction has a positive and significant effect on organizational commitment and organizational citizenship behavior. The result of the research support all hypothesis and indicate that job satisfaction have positive and significant influence to organizational commitment so it is suggested that the Department of Cooperatives and SMEs of Bali Province pay attention to employee job satisfaction to increase organizational commitment and organizational citizenship behavior.